2019
DOI: 10.1002/bab.1797
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D attenuates myocardial ischemia–reperfusion injury by inhibiting inflammation via suppressing the RhoA/ROCK/NF‐ĸB pathway

Abstract: The aim of this study was to investigate the protective effects of vitamin D (VD) against myocardial ischemia–reperfusion (I/R) injury in hearts. An I/R injury model was induced by left coronary artery ligation in Sprague‐Dawley rats (in vivo) and Langendorff perfusion of isolated hearts (in vitro). The infarction areas were determined by triphenyltetrazolium chloride (TTC) staining. Changes in the ST segment, cardiac function, lactate dehydrogenase (LDH) activity, creatine kinase (CK) activity, inflammatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 27 publications
2
19
0
2
Order By: Relevance
“…It down-regulates nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), a transcription factor involved in inflammatory gene expression in lymphocytes [53], and can inhibit its activation by reducing DNA binding of NF-κB [54]. Vitamin D can also dampen inflammation after myocardial injury by inhibiting the RhoA/Rho-associated protein kinase (ROCK)/NF-κB pathway [55]. Furthermore, the VDR/RXR complex binds to the nuclear factor of activated T cells (NFAT) binding site of the IL-2 promoter and inhibits NFAT activity in T cells, thus blocking T cell proliferation [56] and leading to reduced expression of IL-17A [48].…”
Section: Anti-inflammatory Properties Of Vitamin Dmentioning
confidence: 99%
“…It down-regulates nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), a transcription factor involved in inflammatory gene expression in lymphocytes [53], and can inhibit its activation by reducing DNA binding of NF-κB [54]. Vitamin D can also dampen inflammation after myocardial injury by inhibiting the RhoA/Rho-associated protein kinase (ROCK)/NF-κB pathway [55]. Furthermore, the VDR/RXR complex binds to the nuclear factor of activated T cells (NFAT) binding site of the IL-2 promoter and inhibits NFAT activity in T cells, thus blocking T cell proliferation [56] and leading to reduced expression of IL-17A [48].…”
Section: Anti-inflammatory Properties Of Vitamin Dmentioning
confidence: 99%
“…The role of small GTPases in the development of cardiovascular diseases is described [23] . In model animals with ischemia-reperfusion injury inhibitors of RhoA/ROCK signaling pathway demonstrate cardioprotective effect , which is realized through activation of MAPK and NFkB signaling pathways and reduction of Bcl-2 levels leading to a decrease in apoptotic activity of cells [24][25][26][27][28] .…”
Section: Resultsmentioning
confidence: 99%
“…IL-6 and TNF-α can decrease myocyte contractility precisely through the reduction of the systolic calcium level. The experimental study with myocardial ischemia-reperfusion model in rats showed that vitamin D (500 IU/5 day) alleviated myocardial injury considerably with reduced ST segment and infl ammatory cytokine (IL-6), IL-1β, TNF-α) levels (77). In another rat study, vitamin D prevented myocardial infarction by decreasing TNF-α and IL-6 level in isoprenalineinduced myocardial infarction (78).…”
Section: Vitamin D and Cardiovascular Diseasesmentioning
confidence: 98%